Effective elastic thickness in the Central Andes. Correlation to orogenic deformation styles and lower crust high-gravity anomaly. (November 2018) - García, Héctor P.A.; Gianni, Guido M.; Lupari, Marianela N.; Sánchez, Marcos A.; Soler, Santiago R.; Ruiz, Francisco; Lince Klinger, Federico G.
Abstract: Global studies have assessed the importance of elastic thickness ( T e ) on orogenic evolution, showing that the style and nature of upper crustal shortening are influenced by the inherited lithospheric strength. Thus, pioneer works have identified that the upper crustal deformation style in the easternmost sector of the Central Andes in South America are related to the elastic thickness ( T e ). There, the thick-skinned and pure-shear style of Santa Bárbara system was initially related to the existence of low T e values. In contrast, the thin-skinned and simple-shear style of deformation in the Subandean system involves high T e values. However, more recent T e studies in the Central Andes present conflicting results which lead to question this straightforward relation. Results from these studies show a strong dependence on the applied methodology hampering the general understanding of the lithospheric thermo-mechanical state of the Central Andes. To contribute to this issue, we perform a high-resolution T e map, using forward modeling by solving flexural equation of infinite plate model in two dimensions. To achieve this, the crust-mantle interface was calculated using a high-resolution gravity anomaly dataset which combines satellite and terrestrial data, and an average density contrast. Additionally, the gravity anomaly and the foreland basin depth in the Central Andes were best predicted by considering that lower crustal rocks fill the space deflected downward in the plate model. The obtained T e values show an inverse correlation with previous heat flow studies, and a strong spatial correlation with the styles and mechanisms of deformation in the easternmost sector of the Central Andes. In the Santa Bárbara system T e values less than 10 km predominate, whereas in the Subandean system high T e values were observed. Such high values correlate with the orogenic curvature and with an shallower gravity Moho zone, which breaks the regional trend of the Central Andes. This shallower gravity Moho is linked to a high-gravity anomaly located in the east part of the Eastern Cordillera and Subandean system. These results are also correlated with a high-velocity zone in the upper mantle previously found by receiver functions studies. This correlation could indicate changes in the properties of the lower crustal rocks that justify the shallower gravity Moho zone and explain in part the highest T e values. Highlights: Gravity inversion to obtain the geometry of Moho in The Central Andes of South America. Determination of effective elastic thickness from a high resolution gravity dataset (Eigen-6C4 model). Correlation between styles and mechanisms of deformation in the easternmost sector of the Central Andes and the elastic thickness. Inverse correlation between the elastic thickness and heat flow. Shallower gravity Moho linked to a high-gravity anomaly and a high-velocity in the uppermost mantle.